Síntese e caracterização de vanadatos de prata e formação de nanopartículas de prata por eletro-Irradiação - Oliveira, Regiane Cristina de (Universidade Federal de São Carlos, 2018)
Due to its physico-chemical, bactericidal and photocatalytic properties, Silver vanadium oxides (SVOs) have attracted increasing attention due to their excellent physicochemical properties and diverse applications. The aim of this work was to synthesize, by Co-Precipitation (CP) method, SVOs in especial the Ag4V2O7 pyrovanadate. The synthesis methods of this material proposed in the literature, require high temperatures, long processing times and sophisticated equipment. In addition, the final product is obtained with nonhomogeneous sizes and morphologies and containing deleterious phases. In this sense, the objective of this work was to perform an optimization of the CP method, in order to obtain the monophasic Ag4V2O7 with defined morphology. The materials were characterized by X-ray Diffraction (XRD), Rietveld refinement, Raman, Ultraviolet-visible (UV-Vis) and Photoluminescence (PL) spectroscopy. The morphologies of the materials were studied by SEM (Scanning Electron Microscopy). Theoretical calculations of first principles, based on the Functional Density Theory (DFT), were used in the understanding of the experimental observations. Recently, our group reported, for the first time, nucleation and in situ growth of Ag nanoparticles (NPs) on the surface of semiconductors of silver binary oxides, conducted by an electron beam, accelerated under high vacuum (from an electron transmission/scanning microscope) and observed that this phenomenon highlights the properties of this material. Finally, a study of the growth of Ag NPs on the surface of Ag4V2O7 was carried out, the effect of growth of Ag NPs on the electronic properties of the material were evaluated.
Synthesis and characterization of silver vanadates and formation of silver nanoparticles by electro-irradiation
Keywords: Vanadatos de prata; Crescimento de prata; Eletro-irradiação; CIENCIAS EXATAS E DA TERRA::QUIMICA